2009
DOI: 10.1128/jcm.00927-09
|View full text |Cite
|
Sign up to set email alerts
|

False-Positive PCR Detection of Tropheryma whipplei in Cerebrospinal Fluid and Biopsy Samples from a Child with Chronic Lymphocytic Meningitis

Abstract: We report the case of a teenager with chronic lymphocytic meningitis for whom Tropheryma whipplei 16S rRNA PCR results were positive in two cerebrospinal fluid samples and one duodenal biopsy specimen. PCR targeting another specific sequence of Tropheryma whipplei and sequencing of the initially amplified 16S rRNA fragment did not confirm the results. CASE REPORTA 13-year-old boy went to the emergency room with a persistent headache which lasted for 2 weeks and nausea, vomiting, and dizziness. His past medical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 11 publications
0
5
0
Order By: Relevance
“…In contrast, Case 3 who had a positive PCR in CSF in the context of highly suggestive clinical symptoms, and without clinically apparent neurological disease at the time of death had two negative PCR and immunohistochemistry on post-mortem brain tissue, suggesting a good response to an adequate treatment. Although we cannot rule out a false positive result in the latter patient, as it has been previously reported in subjects with other CNS diseases or in healthy individuals (1% to −30% depending on the sample and PCR technique used) (1,8,10,18), the clinical improvement associated with long-term appropriate antibiotic therapy makes this possibility unlikely. The most probable explanation for the posttreatment in vivo and the two post-mortem negative PCR results is to consider that the patient was cured in life by antibiotics without disease reactivation prior to death.…”
Section: Balasa Et Almentioning
confidence: 73%
“…In contrast, Case 3 who had a positive PCR in CSF in the context of highly suggestive clinical symptoms, and without clinically apparent neurological disease at the time of death had two negative PCR and immunohistochemistry on post-mortem brain tissue, suggesting a good response to an adequate treatment. Although we cannot rule out a false positive result in the latter patient, as it has been previously reported in subjects with other CNS diseases or in healthy individuals (1% to −30% depending on the sample and PCR technique used) (1,8,10,18), the clinical improvement associated with long-term appropriate antibiotic therapy makes this possibility unlikely. The most probable explanation for the posttreatment in vivo and the two post-mortem negative PCR results is to consider that the patient was cured in life by antibiotics without disease reactivation prior to death.…”
Section: Balasa Et Almentioning
confidence: 73%
“…PCR testing of cerebrospinal fluid specimens for T. whipplei in neurological patients is clinically reasonable, as the disease is fatal without specific treatment. As is the case for all diagnoses performed using PCR, caution is necessary, and a rigorous strategy should be applied when performing and interpreting the analyses due to the risk of false-positive results [ 58 ]. A carefully checked positive PCR in cerebrospinal fluid specimens is sufficient for diagnosis.…”
Section: Discussionmentioning
confidence: 99%
“…They concluded that qPCR on stool and saliva samples is a good initial screening method (40). However, it is critical to validate the specificity of the PCR, as false-positive PCR results on saliva has been reported, especially when using 16S rRNA gene-based primers as the T. whipplei 16S rRNA genes are very similar to those of other bacteria that can be present in the oral cavity (183,187). Wholegenome sequencing of T. whipplei identified more-specific PCR targets like the repetitive sequences, which when used in addition to other targets helped to rule out false-positive results (186,188).…”
Section: Histopathology (Pas and Hematoxylin-and-eosin Stain [Hande]mentioning
confidence: 99%
“…It is advisable that in atypical cases of T. whipplei, two different specific target genes are tested and that the results for both target genes should be positive in order to rule out potential false-positive results (51,183). The occurrence of false-positive PCR results has been reported, e.g., in cerebrospinal fluid samples and duodenal biopsy specimens (187). In order to minimize the chance of false-positive results caused by contamination or due to a nonspecific PCR, qPCR should preferably be performed on more than one sample and whenever possible also include invasive samples, for instance, blood or biopsy specimen (40).…”
Section: Histopathology (Pas and Hematoxylin-and-eosin Stain [Hande]mentioning
confidence: 99%